Razmislek o retroaktivni uporabi spremenjene sodne prakse glede pojasnilne dolžnosti pri sklepanju kreditnih pogodb v švicarskih frankih - Pirnat, Rajko (Javna uprava, 2023)
The author notes that three 2023 decisions of the Supreme Court, namely the judgments in the cases II Ips 8/2022 of 19 April 2023 and II Ips 49/2023 of 18 October 2023 and the judgment and decision in the case II Ips 54/2023 of 20 September 2023, mark a significant shift in jurisprudence regarding the explanatory duty of banks when concluding credit agreements in Swiss francs. Previously, neither the laws nor their interpretation, nor other relevant circumstances at the time of contract conclusion, mandated such an implementation of the duty to explain, as derived from the Supreme Court’s case law. This implies that the new Supreme Court case law in these cases is applied retroactively, i.e. to cases that occurred fifteen years before the establishment of this new practice. The author notes that both legal doctrine and case law employ the criterion of reasonable foreseeability in determining the permissibility of retroactively applying a new judicial interpretation of the law. Retroactive application is only permissible if it adversely affects a party’s position and if, at the time of the party’s legally significant actions, they could have reasonably anticipated the future judicial interpretation of the law concerning these actions. Upon reviewing all relevant circumstances, the author believes that, based on an objective assessment, it cannot be claimed that even fifteen years ago, banks could have reasonably foreseen the stringent requirements of the duty to explain as it appears in the Supreme Court’s recent case law. Moreover, the author highlights that the Supreme Court, in the aforementioned judgments, did not even consider the issue of retroactive application of this case law, thereby failing to justify its view that such retroactive application of new case law is permissible in these cases. This omission constitutes a deficient reasoning of court decisions and thus a violation of Article 22 of the Constitution.
Keywords: banke; krediti; kreditne pogodbe; Slovenija; sodna praksa; ustavno pravo